Effects of pH on the physicochemical properties of MoVTeNbOx catalysts for oxidation of propane - Mohd Noor, Syazwani (2015)
Mo0.1V0.3Te0.23Nb0.12 mixed metal oxide catalysts were prepared via slurry method followed by microwave irradiation. The effect of pH was studied by varying the pH of the resultant solution at pH = 1.0, 3.0. 5.0 and 7.0 (± 0.01). The catalysts precursor obtained were calcined for 1 h in air at 553 K and 2 h in N2 stream at 873 K. The catalysts were post treated by washing with 30% H2O2. An Anderson-type heteropolyanion was formed in samples prepared at pH 3.0–7.0 (±0.01). After calcination, X-ray Diffraction Analysis (XRD) explained that the active orthorhombic M1 phase was obtained for samples prepared at lower pH (pH 1.0 and pH 3.0 (±0.01)). From Fourier Transform-Infrared (FT-IR) spectra, no significant difference in the formation of functional group of different synthesised pH of the MoVTeNbOx catalysts. Thermo Gravimetry-Differential Thermal Gravimetric Analysis (TG-DTG) for all samples show a similar thermal behaviour with four decomposition signals. Inductive Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES) revealed that a remarkable loss of tellurium was observed after calcination. The catalysts borne rodshaped morphology under Field Emission-Scanning Electron Microscopy (FE-SEM). XRD analysis after post treatment suggested the elimination of hexagonal M2 phase and modification of orthorhombic M1 crystal surfaces. Washing with hydrogen peroxide also gave better reducibility of the catalysts in Temperature Programmed Reduction in Hydrogen (H2-TPR) by shifting the peak maximum to lower temperature compared to the unwashed catalysts. Brunauer-Emmett-Teller surface area analysis (SBET) exposed that the catalysts prepared at lower pH value has a higher surface area than catalysts prepared at higher pH value. Overall, the catalytic study of MoVTeNbOx catalysts revealed that catalyst prepared at pH 1.0 (±0.01) has high selectivity towards acrylic acid in anaerobic oxidation of propane. Thus, the different synthesis pH has a strong effect on the final phase composition and distinct activities of MoVTeNbOx catalysts.